ITIL - Information Technology Infrastructure Library: fundamentos em service support - BALAM, Edgard Henrique (004, 2007)
A ITIL é basicamente um conjunto de boas práticas desenvolvidas no setor de IT, onde teoria e prática nos serviços de IT, nem sempre estão no mesmo compasso. Este trabalho tem como finalidade, expor a metodologia que compõe o Information Technology Infrastructure Library — ITIL, o conceito, objetivos e benefícios que a implementação do método na infra-estrutura de IT traz para a Organização, usuário e parceiros da companhia, relacionando a teoria com a prática dentro dos serviços prestados de IT. Com foco principal na disciplina de Service Support, o trabalho abrange os fundamentos dos processos de Gerenciamento de Configuration, Incident, Problem, Change, Release e as funções do Service-Desk. O conjunto desses processos e funções e as suas inter-relações, fazem da disciplina de Service Support, uma importante e fundamental ferramenta aplicada a Infra-Estrutura de IT da Organização melhorando a qualidade dos serviços prestados de IT

ITIL is basically a set of good practices developed in the IT department, where theory and practice are not always in the same wave length. This work has the purpose of exposing the methodology that composes the Information Technology Infrastructure Library (ITIL) , apart from the concept, objectives and benefits that the implementation of the method in the infrastructure of the IT brings to the organization, users and partners of the company, relating the theory to the practice in the services rendered by the IT. With the main focus on the subject of Service Support, the work comprehends the fundaments of the Configuration Management, Incident, Problem, Change, Release, as well as the functions of the Service Desk. These processes, together with the functions, and inter- relations turn the Service Support subject into an important and fundamental tool applied to the IT infrastructure of the organization, improving the quality of the services rendered by this department.
ITIL - Information Technology Infrastructure Library: fundamentals in service support
Keywords: Informação; Tecnologia da informação; Infraestrutura; Informação e Comunicação